2020
DOI: 10.4018/jgim.2020070106
|View full text |Cite
|
Sign up to set email alerts
|

IT Application Maturity in China

Abstract: In order to investigate the relationship between IT application maturity and management capabilities, the authors conducted a survey study to collect related company information for analysis. Data processing was conducted to obtain valid and reliable variables representing IT application maturity, management institutional capability, and process management capability. Then, they adopted a partial differential equation approach to capture the time dynamics of these variables. The equations were solved analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…In contrast to other aspects, such as cast and screenplay, it is relatively difficult to experience the special effects of a movie at home. Peng et al (2020) indicated that the achievement of information technology (IT) maturity represented business' management capabilities. From this point of view, BDA could help companies make better decisions and have a positive impact on profit.…”
Section: Managerial Implicationmentioning
confidence: 99%
“…In contrast to other aspects, such as cast and screenplay, it is relatively difficult to experience the special effects of a movie at home. Peng et al (2020) indicated that the achievement of information technology (IT) maturity represented business' management capabilities. From this point of view, BDA could help companies make better decisions and have a positive impact on profit.…”
Section: Managerial Implicationmentioning
confidence: 99%
“…IT objects enable firms to share information and knowledge across organizational boundaries, IT knowledge improves the level of information perceived by firms and IT operations improve the information processing capabilities of firms (Chakravarty et al, 2013;Chae et al, 2014;Eskelund et al, 2020;Hanafizadeh and Zareravasan, 2020;Lu and Ramamurthy, 2011). Prior studies have identified IT capability as an important resource for firms to maintain continuity of supply chain operations, enabling them to deal quickly with unforeseen events and compete successfully in a volatile environment (Babin et al, 2020;Chang et al, 2020;Chen et al, 2017;Lu and Ramamurthy, 2011;Peng et al, 2020). Accordingly, the current study intends to specifically document IT capability's effect on SCR.…”
Section: Introductionmentioning
confidence: 99%
“…IT technology has been widely used in enterprise management practice (Ensslin et al, 2019;Peng et al, 2020). As an inevitable development result of artificial intelligence, agent and multi-agent have attracted attention and concern in the academic research, and are widely used in various fields (Morrar et al, 2019;Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%